ВПЛИВ З’ЄДНУВАЛЬНОГО КАНАЛУ КУЯЛЬНИК – ЧОРНЕ МОРЕ НА ПОКАЗНИКИ ЗООПЛАНКТОНУ - Мігас, Р.В. (Marine Ecological Journal, 2023)
Changes in the qualitative and quantitative indicators of mesozooplankton in seawater flowing through a special channel from the Odessa Bay of the Black Sea to the Kuyalnytsya estuary are considered in order to maintain the permissible level of salinity. This is the first study in the world of the impact of a high-velocity canal on zooplankton for seawater. In 2017, during the operation of the connecting channel (in the cold water period), a comparison of zooplankton indicators was performed at sea and at the exit from the channel. As a result of passing through the canal, the quantitative indicators of zooplankton decreased by an order of magnitude: the number at sea – 18372 ind. ∙ m-3 and at the exit from the canal – 398 ind. ∙ m-3; biomass – 60.0 mg ∙ m-3 and 2.0 mg ∙ m-3, respectively. The percentage of losses fluctuated by seasons and ranged from 41% (April) to 99% (February) in number, and from 27% (March) to 99% (February and December) in biomass. Such a large run was associated with changes in the qualitative composition of zooplankton. Zooplankton of the study period was represented by 11 taxa. Its constant component at sea and at the exit of the canal was Acartia clausi + tonsa. In some months, the following representatives of zooplankton were present only in the sea: in April, the eutrophic indicator Noctiluca scintillans (Macartney) Kofoid & Swezy, 1921 (40 ind. ∙ m-3, 1.8962.0 mg ∙ m-3), and – Rissoa splendida Eichwald, 1830 (20 ind. ∙ m-3, 0.140 mg ∙ m-3), and in February – rotifers of the genus Keratella (1400 ind ∙ m-3, 0.700 mg ∙ m-3). All these species did not tolerate passage through the channel: N. scintillans